Taktik Pengaruh Dan Hubungannya Dengan Gaya Kepimpinan Pensyarah Institusi Pengajian Tinggi - Noor Asmahan Abdullah; Mua azam Mohamad (International Consortium of Education and Culture Research Studies, 2019)
Mastering the tactics of influence in leadership practices is important in able to impact the culture and relationships of fellow citizens in the organization. Hence, leaders need to know how to use appropriate tactics of subordinates to reduce conflict in leadership, especially in higher education. The purpose of this study is to identify the most frequently used influence tactics as well as to identify the relationship of influence tactics and leadership styles. This descriptive study involve sample of 150 polytechnic lecturers in Kelantan. The quantitative data of the study were collected by cross-sectional use of Influence Behavior Questionnaire and Multifactor Leadership Questionnaire. The findings show that soft influence tactics are most often used than hard influence tactics. The findings also show that the tactics of influence have a significant relationship with the transformational leadership style compared to the transactional leadership style and the laissez faire. It is important for a leader of an educational institution to identify appropriate influence tactics based on the institutional situation and environment.